Lenvatinib plus pembrolizumab in patients with either treatment-naive or previously treated metastatic renal cell carcinoma (Study 111/KEYNOTE-146): a phase 1b/2 study. Issue 7 (July 2021) - Lee, Chung-Han; Shah, Amishi Yogesh; Rasco, Drew; Rao, Arpit; Taylor, Matthew H; Di Simone, Christopher; Hsieh, James J; Pinto, Alvaro; Shaffer, David R; Girones Sarrio, Regina; Cohn, Allen Lee; Vogelzang, Nicholas J; et al.
Summary: Background: Despite advances in the first-line treatment of metastatic renal cell carcinoma (RCC), there is an unmet need for options to address disease progression during or after treatment with immune checkpoint inhibitors (ICIs). Pembrolizumab and lenvatinib are active as monotherapies in RCC; thus, we aimed to evaluate the combination of lenvatinib plus pembrolizumab in these patients. Methods: We report results of the metastatic RCC cohort from an open-label phase 1b/2 study of lenvatinib plus pembrolizumab in patients aged at least 18 years with selected solid tumours and an Eastern Cooperative Oncology Group performance status of 0–1. Oral lenvatinib at 20 mg was given once daily along with intravenous pembrolizumab at 200 mg once every 3 weeks. Patients remained on study drug treatment until disease progression, development of unacceptable toxicity, or withdrawal of consent. Efficacy was analysed in patients with clear cell metastatic RCC receiving study drug by previous therapy grouping: treatment naive, previously treated ICI naive (previously treated with at least one line of therapy but not with an anti-PD-1 or anti-PD-L1 ICI), and ICI pretreated (ie, anti-PD-1 or anti-PD-L1) patients. Safety was analysed in all enrolled and treated patients. The primary endpoint was the objective response rate at week 24 per immune-related Response Evaluation Criteria In Solid Tumors (irRECIST) by investigator assessment. This trial is registered with ClinicalTrials.gov (NCT02501096 ) and with the EU Clinical Trials Register (EudraCT2017-000300-26), and is closed to new participants. Findings: Between July 21, 2015, and Oct 16, 2019, 145 patients were enrolled in the study. Two patients had non-clear cell RCC and were excluded from the efficacy analysis (one in the treatment-naive group and one in the ICI-pretreated group); thus, the population evaluated for efficacy comprised 143 patients (n=22 in the treatment-naive group, n=17 in the previously treated ICI-naive group, and n=104 in the ICI-pretreated group). All 145 enrolled patients were included in the safety analysis. The median follow-up was 19·8 months (IQR 14·3–28·4). The number of patients with an objective response at week 24 by irRECIST was 16 (72·7%, 95% CI 49·8–89·3) of 22 treatment-naive patients, seven (41·2%, 18·4–67·1) of 17 previously treated ICI-naive patients, and 58 (55·8%, 45·7–65·5) of 104 ICI-pretreated patients. Of 145 patients, 82 (57%) had grade 3 treatment-related adverse events and ten (7%) had grade 4 treatment-related adverse events. The most common grade 3 treatment-related adverse event was hypertension (30 [21%] of 145 patients). Treatment-related serious adverse events occurred in 36 (25%) patients, and there were three treatment-related deaths (upper gastrointestinal haemorrhage, sudden death, and pneumonia). Interpretation: Lenvatinib plus pembrolizumab showed encouraging antitumour activity and a manageable safety profile and might be an option for post-ICI treatment of metastatic RCC. Funding: Eisai and Merck Sharp & Dohme.